2021
DOI: 10.1101/2021.09.08.459369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic fluctuations affect circadian patterns of locomotor activity in zebrafish

Abstract: The locomotor activity of zebrafish (Danio rerio) has a pronounced, well-studied circadian rhythm. Under constant illumination, the period of free-running locomotor activity in this species usually becomes less than 24 hours. To evaluate the entraining capabilities of slow magnetic variations, zebrafish locomotor activity was evaluated at constant illumination and fluctuating magnetic field with a period of 26.8 hours. Lomb-Scargle periodogram revealed significant free-running rhythms of locomotor activity and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Lighting conditions were reported in all studies in the review and strategies were evenly split with 14 studies (51.85%) using a regimen of 14/10 hours light/dark cycle and 13 (48.15%) with 12/12 hours light/dark cycle. This is an additional criterion to be standardized in other to optimize the evaluation of desired effects without the interference of the light/dark cycle since the circadian cycle has a direct impact on physiology and behavior (Kopp et al, 2018;Krylov et al, 2021).…”
Section: Ee Protocols In Zebrafishmentioning
confidence: 99%
“…Lighting conditions were reported in all studies in the review and strategies were evenly split with 14 studies (51.85%) using a regimen of 14/10 hours light/dark cycle and 13 (48.15%) with 12/12 hours light/dark cycle. This is an additional criterion to be standardized in other to optimize the evaluation of desired effects without the interference of the light/dark cycle since the circadian cycle has a direct impact on physiology and behavior (Kopp et al, 2018;Krylov et al, 2021).…”
Section: Ee Protocols In Zebrafishmentioning
confidence: 99%
“…Behavioral diversity can be displayed in many forms including differences in overall activity, responses to stimuli, and social interactions 17,28 and is also highly prominent in diel rhythms of behavior 29,30 . Studies in terrestrial organisms, like drosophilid flies, identified differences in the expression of circadian clock genes and the neuropeptide pigmentdispersing factor (PDF) to be responsible for species-and population-specific patterns of diel activity 3,20,21,[31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the exposure of larvae to the same magnetic fields between 11 and 14 days post fertilization led to the desynchronization of Cry1aa and Per1b circadian oscillations [ 22 ]. Moreover, preliminary data on the entraining of zebrafish circadian rhythms by magnetic oscillations with a period of 26.8 h are available [ 23 ].…”
Section: Introductionmentioning
confidence: 99%